2022
DOI: 10.1038/s41398-022-02002-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic disturbances, hemoglobin A1c, and social cognition impairment in Schizophrenia spectrum disorders

Abstract: Social cognitive impairments are core features of schizophrenia spectrum disorders (SSD) and are associated with greater functional impairment and decreased quality of life. Metabolic disturbances have been related to greater impairment in general neurocognition, but their relationship to social cognition has not been previously reported. In this study, metabolic measures and social cognition were assessed in 245 participants with SSD and 165 healthy comparison subjects (HC), excluding those with hemoglobin A1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Recently, Tang et al investigated the link between social cognition impairment and metabolic disturbances in patients with schizophrenia spectrum disorders and they reported a robust relationship between abnormal glucose metabolism and social cognition. Moreover, the correlation with social cognition and glucose abnormality was stronger than for non-social cognition 42 . Similarly, our results are important to support the idea of there is a relationship between metabolic dysregulation and impaired social cognition in patients with BD.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Recently, Tang et al investigated the link between social cognition impairment and metabolic disturbances in patients with schizophrenia spectrum disorders and they reported a robust relationship between abnormal glucose metabolism and social cognition. Moreover, the correlation with social cognition and glucose abnormality was stronger than for non-social cognition 42 . Similarly, our results are important to support the idea of there is a relationship between metabolic dysregulation and impaired social cognition in patients with BD.…”
Section: Discussionmentioning
confidence: 79%
“…First, BD is linked with increased inflammation and may cause metabolic abnormalities and decreased social cognition performance. Second, metabolic dysfunction causes large vessel and microvascular changes that damage cerebral circulation and brain structure 42 . However, social cognition requires more complex integration of multiple cognitive systems than nonsocial cognition, making it more susceptible to disruptions in connectivity 43 .…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that metabolic dysfunction plays a key role in the etiopathogenesis of schizophrenia [13,21,55,59]. Alterations in glucose utilization, secondary to perturbed insulin signaling pathways, likely contributes to the cognitive deficits seen in schizophrenia [12,60,61]. AKT activity is dependent on activation of upstream growth factor (such as insulin) receptor occupancy and activation [21,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…There was no association between HbA1c and cognitive impairment. Previous studies have suggested a correlation between HbA1c level and poor cognition in recent onset psychosis patients [ 58 , 59 ]. Most of the previous results were found in patients with diabetes or in elderly population [ 60 , 61 ], and with differences in race among the included subjects.…”
Section: Discussionmentioning
confidence: 99%